John Paul II, Dialogue with Muslims and the Question of Religious Freedom - Olizar, Isabel (The Downside review, 2021)
John Paul II was committed to dialogue with Muslims, and to the defence of religious freedom. This article reflects upon how John Paul II held these commitments together as threats to religious freedom from within the Muslim World emerged during his papacy. This article argues that the central theological insight of the Council, that Christians and Muslims together adore the one God, provided a framework into which John Paul II brought deepening reflections on the different ways in which Christians and Muslims understand God, the person and truth and freedom. In his dialogue with Muslims, John Paul II witnessed to the Christian understanding of human dignity and set out a theologically grounded defence of religious freedom.